Empowering Rehabilitation: An Exploration of Legal Counselling's Role in Female Inmate Assimilation at Indonesian Penitentiaries - Fitri Wahyuni; Siti Rahmah; Syarifuddin Syarifuddin (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to examine the implementation of community service activities as part of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education) by lecturers, focusing on legal counseling on Islamic law for female inmates at Class II A Tembilahan Penitentiary. The research employs a direct field approach, offering lectures related to Islamic law and providing counseling opportunities. It spans over a period from January 2023 to March 2023. The findings indicate a noticeable increase in legal awareness and a potential for assimilation among female convicts, contributing to their mental development and promoting repentance. These measures are anticipated to result in a deterrent effect, preventing the recurrence of past transgressions. The implications of this research underline the crucial role of academic involvement in penitentiaries, specifically highlighting the impact of integrating the teaching of Islamic law into the rehabilitation of female convicts. Highlights: Implementation of legal counseling by academic lecturers contributes significantly to the increase of legal awareness among female inmates at Class II A Tembilahan Penitentiary. Lectures on Islamic law over a three-month period contributed to noticeable mental development and a sense of repentance among the inmates. The integration of academic community services in penitentiaries presents a potential deterrent effect and reduces the chances of inmates repeating past transgressions. Keywords: Legal Counseling, Islamic Law, Female Inmates, Rehabilitation, Assimilation